Анализ качества речи в корпоративных сетях спутниковой связи - Гулякова, Т. Б. (ХНУРЭ, 2009)
In research work the possibility of provision of a speech transmission on corporate satellite networks is parsed. The component delays and their influence to quality of transmitted speech are researched.
Keywords: анализ качества речи; корпоративные сети спутниковой связи